2023
DOI: 10.1038/s41467-023-36001-5
|View full text |Cite
|
Sign up to set email alerts
|

Rapid transmission and tight bottlenecks constrain the evolution of highly transmissible SARS-CoV-2 variants

Abstract: Transmission bottlenecks limit the spread of novel mutations and reduce the efficiency of selection along a transmission chain. While increased force of infection, receptor binding, or immune evasion may influence bottleneck size, the relationship between transmissibility and the transmission bottleneck is unclear. Here we compare the transmission bottleneck of non-VOC SARS-CoV-2 lineages to those of Alpha, Delta, and Omicron. We sequenced viruses from 168 individuals in 65 households. Most virus populations h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…We compared the estimates we obtained for the probability p from our simulation approach with those stemming from the analysis of household transmission pair data (for both seasonal influenza (49) and SARS-CoV-2 (50)). From the data publicly available associated with the work of McCrone et al (49), we identified 38 H3N2 transmission pairs (23 had identical consensus sequences).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared the estimates we obtained for the probability p from our simulation approach with those stemming from the analysis of household transmission pair data (for both seasonal influenza (49) and SARS-CoV-2 (50)). From the data publicly available associated with the work of McCrone et al (49), we identified 38 H3N2 transmission pairs (23 had identical consensus sequences).…”
Section: Methodsmentioning
confidence: 99%
“…%! − 1) -the probability that transmission occurs before mutation -the dispersion parameter -the reproduction number of the non-variant -the number of clusters simulated for both the variant and the non-variant (50,100,1000,5000) For each combination of parameters, we evaluated the sensitivity of our statistical framework in detecting a difference between the reproduction numbers of two genetic subpopulations. This was done running our inference framework on 100 different datasets generated using the same set of parameters.…”
Section: Simulation Study To Evaluate the Performance Of Our Inferenc...mentioning
confidence: 99%
“…Accurate quantification of the transmission bottleneck size is essential, as it impacts the genetic diversity of recipient hosts and the rate of pathogen adaptation 35 . It is known that while narrow transmission bottlenecks correspond to a low frequency of transmitted iSNVs, wide ones ensure that beneficial variants are maintained 36 . Transmission bottleneck sizes and directionality were calculated using the Beta‐binomial inference method and taking into consideration the date of sample collection and the working relationship between the subjects.…”
Section: Resultsmentioning
confidence: 99%
“…35 It is known that while narrow transmission bottlenecks correspond to a low frequency of transmitted iSNVs, wide ones ensure that beneficial variants are maintained. 36 Transmission bottleneck sizes and directionality were calculated using the Beta-binomial inference method and taking into consideration the date of sample collection and the working relationship between the subjects. In total, we performed Indeed, when we examined the Cluster 5, whose swabs were collected in the same day, soon after the symptom onset, and the direct contact is well known, we observed a much larger bottleneck (range 174-200 Nb) as compared with those observed in patients with known direct contact but sampled at a longer time interval (5 days) (range 37-79 Nb), as in the case of patients S02 and S03, or in Cluster 1, where indirect contact can be assumed.…”
Section: Transmission Bottlenecks Evaluationmentioning
confidence: 99%
“…Genomic data has shown that for influenza and SARS-CoV-2 infection, the transmission bottleneck generally involves few viral particles [1][2][3][4] . This tight bottleneck limits the role of within-host evolution; variants need to be generated de novo before selection at that scale can take effect…”
Section: Introductionmentioning
confidence: 99%